Opening the black box: A mixed-methods investigation of social and psychological mechanisms underlying changes in financial behaviour - Steinert, JI; Cluver, LD; Meinck, F; Nzima, D; Doubt, J (Taylor & Francis (Routledge), 2020)
We use a mixed-methods approach to open the ‘black box’ of a combined financial literacy and parenting intervention (‘Parenting for Lifelong Health’) to elucidate the key mechanisms through which changes in financial behaviour are realised. Drawing on qualitative data from 16 focus groups and 42 in-depth interviews, we find evidence for three pathways of change. Higher financial skills and, linked to this, higher financial confidence, a more optimistic future outlook and emotional support provided by peers and family members are described as key facilitators of improved financial behaviour. These mechanisms are cross validated in subsequent quantitative analyses based on standardised interviews from a randomised controlled trial with 552 households. A mediation analysis indicates that the programme’s effect on financial behaviour is significantly mediated by financial skills and self-efficacy (24% of total effect) and optimism (22% of total effect). We further show that the psychological factors are significantly reinforced by increased levels of social support in the family and wider community. Mediating variables remain robust in sensitivity analyses and are confirmed as significant paths when entered simultaneously into a structural equation path model. Our findings highlight possible target points for financial literacy interventions and motivate the inclusion of psychosocial programme components.